The Early Bronze Age in the Hajar oases: new investigations of the settlement, funerary and monumental site of al-Dhabi 2 (Bisya, Oman) - Jean, Mathilde; Sauvage, Martin; Munoz, Olivia; de Castéja, Victoria; Mespoulet, Théo; Pinot, Josselin; Rointru, Kaïna (Proceedings of the Seminar for Arabian Studies, 2023)
The development of monumental architecture (oasis towers), organised settlements, and new funerary structures are markers of the emergence of social complexity in the culture of Magan in the Hafit and Umm an-Nar periods. Bisya is one of the largest sites in central Oman where this phenomenon may be observed. The French Archaeological Mission in central Oman (FAMCO) is undertaking a new research program at al-Dhabi 2 (Bisya, ad-Dakhiliyah, Oman), a site gathering EBA monumental, settlement, and funerary architecture. In 2022, the complete plan of the structures unveiled the site's organisation, with a large tower on a hill, a built settlement area in the foothills, and several Hafit and Umm an-Nar tombs. Excavations were carried out in the settlement area (150 m²) to study architecture and confirm the domestic nature of the remains. The pottery assemblage is typical of the Umm an-Nar period; however, we may have reached earlier occupation layers. Finally, two excavated tombs yielded preliminary results on the funerary landscape at Early Bronze Age Bisya. This project opens up broad perspectives for future research at al-Dhabi to understand the social and cultural evolution of protohistoric communities in southeast Arabia better.